1986
DOI: 10.1038/bjc.1986.157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of passive smoking to risk of lung cancer and other smoking-associated diseases

Abstract: SummaryIn the latter part of a large hospital case-control study of the relationship of type of cigarette smoked to risk of various smoking-associated diseases, patients answered questions on the smoking habits of their first spouse and on the extent of passive smoke exposure at home, at work, during travel and during leisure. In an extension of this study an attempt was made to obtain smoking habit data directly from the spouses of all lifelong non-smoking lung cancer cases and of two lifelong non-smoking mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
86
1
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(89 citation statements)
references
References 17 publications
1
86
1
1
Order By: Relevance
“…To ensure completeness, we reviewed published and unpublished studies of nonfatal myocardial infarction (MI) and/or death from ischemic heart disease (IHD) among lifelong nonsmokers whose potential ETS exposure was defined by the smoking status of the spouses. Ultimately we included nine cohort (3,4,(6)(7)(8)(9)(10)(11)(12)(13) and eight case-control (14)(15)(16)(17)(18)(19)(20)(21)(22) studies in the overview. Two of the cohort studies (3,4) and three case-control studies (20)(21)(22) were new since OSHA last summarized the literature (5).…”
Section: Methodsmentioning
confidence: 99%
“…To ensure completeness, we reviewed published and unpublished studies of nonfatal myocardial infarction (MI) and/or death from ischemic heart disease (IHD) among lifelong nonsmokers whose potential ETS exposure was defined by the smoking status of the spouses. Ultimately we included nine cohort (3,4,(6)(7)(8)(9)(10)(11)(12)(13) and eight case-control (14)(15)(16)(17)(18)(19)(20)(21)(22) studies in the overview. Two of the cohort studies (3,4) and three case-control studies (20)(21)(22) were new since OSHA last summarized the literature (5).…”
Section: Methodsmentioning
confidence: 99%
“…Some of these studies showed a clear association of passive smoking with lung cancer (Cornea et al 1983;Garfinkel et al 1985;Akiba et al 1986;Inoue et al 1986). However, the results of other studies were equivocal or negative (Garfinkel 1981 Lee et al 1986). …”
mentioning
confidence: 74%
“…I Detailed descriptions of the Evans County study design and the 20-year mortality follow-up of the cohort have been reported elsewhere. [1][2][3][4][5][6][7][8][9][10][11][12][13] At baseline, 554 (82 percent) White and 389 (83 percent) Black women, among a total of the 1,127 women ages 40-74, reported that they had never smoked. The present study was restricted to the 328 White women and 185 Black older women who had never smoked and were married to male examinees who reported they either had never smoked or were current smokers at baseline.…”
Section: Methodsmentioning
confidence: 99%